2018
DOI: 10.1111/jbi.13452
|View full text |Cite
|
Sign up to set email alerts
|

Functionally richer communities improve ecosystem functioning: Dung removal and secondary seed dispersal by dung beetles in the Western Palaearctic

Abstract: Aim In several ecosystems, the diversity of functional species traits has been shown to have a stronger effect on ecosystem functioning than taxonomic diversity alone. However, few studies have explored this idea at a large geographical scale. In a multisite experiment, we unravelled the relationship between ecosystem function and functional completeness of species assemblages using dung beetles as a model group, focusing on dung removal and secondary seed dispersal. Location Seventeen grassland locations acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 53 publications
(82 reference statements)
5
45
0
Order By: Relevance
“…This is in accordance with other experiments carried out in tropical and boreal habitats and shows the general importance of tunnellers for ecosystem functioning (Slade et al ., ; Kaartinen et al ., ). This is particularly the case for most Central European regions where roller species are absent and tunnellers are the most effective group from a functional perspective (Milotić et al ., ). In our experiment, tunneller biomass varied up to 165‐fold between locations in autumn and up to 315‐fold in summer.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This is in accordance with other experiments carried out in tropical and boreal habitats and shows the general importance of tunnellers for ecosystem functioning (Slade et al ., ; Kaartinen et al ., ). This is particularly the case for most Central European regions where roller species are absent and tunnellers are the most effective group from a functional perspective (Milotić et al ., ). In our experiment, tunneller biomass varied up to 165‐fold between locations in autumn and up to 315‐fold in summer.…”
Section: Discussionmentioning
confidence: 97%
“…There were only weak effects of species richness, abundance, and no effect of functional diversity on dung removal in the habitats studied, although positive relationships were reported from mesocosm experiments and from field studies elsewhere (Slade et al ., ; Beynon et al ., ; Dangles et al ., ; Gollan et al ., ; Milotić et al ., ). However, mesocosm experiments with species from temperate habitats showed that the loss of abundance has a larger effect on dung removal than did species loss (Manning & Cutler, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To preserve dung beetle assemblages and their ecosystem functions, conservation strategies in tropical forests should prioritise reduction in deforestation or logging and an increase in the environmental heterogeneity (Sánchez-de-Jesús et al, 2016;Edwards et al, 2017). Sensitive management will increase biological diversity and hence functional diversity as a result of habitat adaptation or habitat preference of species to different environments (Milotić et al, 2019). In the FEA, a managed logging forest, caution should be taken to avoid the occurrence of clearings close to logging areas (Edwards et al, 2017) because both have strong effects on the forest and biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, environmental changes strongly affect the performance of their ecological functions (Braga et al, 2013;Gray et al, 2014). However, there is functional importance with respect to maintaining a species-rich dung beetle assemblage even in the absence of perturbations to the system, which is expected to buffer ecosystem services in disturbed ecosystems (Beynon et al, 2012;Milotić et al, 2019). The habitat specificity found in dung beetles prevents several forest-dependent species to inhabit open habitats (Klein, 1989;Noriega et al, 2007;Silva et al, 2016) as a result of changes in microclimatic conditions along the open-forest habitat gradient (Feer, 2008).…”
Section: Introductionmentioning
confidence: 99%